Case Study: Application Of Slow Deep Breathing Intervention In Post-CABG Coronary Artery Disease Patients With Acute Pain Nursing Problems - ALMAY RAYHAN ARRAFI; Ristina Mirwanti; Aan Nuraeni (Universitas Padjadjaran, 2022)
Coronary Artery Disease (CAD) is a cardiovascular disease. Coronary Artery Bypass Graft (CABG) is a revascularization therapy in CHD which causes side effects in the form of pain which can worsen the patient's health if left untreated. The use of pharmacological therapy requires additional therapy such as non-pharmacological therapy to support the success of the pharmacological therapy that has been given. Slow Deep Breathing has the potential to be an intervention that nurses can perform to efficiently manage pain. The purpose of writing this article is to report on the implementation of Slow Deep Breathing (SDB) interventions in patients with CHD after the Coronary Artery Bypass Grafting procedure with acute pain nursing problems. There was a 66-year-old patient with a history of CAD who had performed the second day of the CABG procedure and experienced chest pain after CABG surgery accompanied by tightness. Slow Deep Breathing given for 15 minutes every time the patient feels pain can potentially be an additional pain management intervention for patients with post-CABG chest pain.